2017
DOI: 10.1111/jpn.12613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laboratory‐isolated Lactobacillus plantarum LGFCP4 from gastrointestinal tract of guinea fowl on growth performance, carcass traits, intestinal histomorphometry and gastrointestinal microflora population in broiler chicken

Abstract: The study aimed to investigate the effect of feed supplements, viz Lactobacillus plantarum LGFCP4 (laboratory isolate from GIT of Guinea fowl), Lactobacillus acidophilus (NCDC, Karnal) and in-feed antibiotic bacitracin methylene disalicylate (BMD) on growth performance, FCR, carcass traits and immune organs weight, intestinal histomorphometry and gastrointestinal microflora population in broiler chickens. In a completely randomized design, CARIBRO-Dhanraja broiler chicks (n = 160) were used with four treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
(25 reference statements)
2
17
0
Order By: Relevance
“…Production parameters are often used for the evaluation of the influence of synbiotics and probiotics on the health of broiler chickens. Many experimental models have shown that these nutritional supplements usually improve the performance of broiler chickens, but the results depend on the type of synbiotic used [1,10,11,13,15,16,18,21,[32][33][34][35][36][37][38][39][40][41][42][43]. Usually, these parameters are measured at the end of the production cycle but, to improve the quality of analysis, we decided to measure them at several time points.…”
Section: Growth Performance Of Broilersmentioning
confidence: 99%
See 1 more Smart Citation
“…Production parameters are often used for the evaluation of the influence of synbiotics and probiotics on the health of broiler chickens. Many experimental models have shown that these nutritional supplements usually improve the performance of broiler chickens, but the results depend on the type of synbiotic used [1,10,11,13,15,16,18,21,[32][33][34][35][36][37][38][39][40][41][42][43]. Usually, these parameters are measured at the end of the production cycle but, to improve the quality of analysis, we decided to measure them at several time points.…”
Section: Growth Performance Of Broilersmentioning
confidence: 99%
“…According to the currently most accepted definition, probiotics are single-or multi-component preparations containing live microorganisms that, when administered in appropriate numbers, bring health benefits to the host [12]. Probiotics improve the microbiological balance of intestines and strengthen the intestinal barrier against the influence of harmful factors [13]. Prebiotics are preparations containing indigestible nutrients that favorably affect the growth and/or activity of one or more intestinal bacterial species [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the probiotics can affect the expression of genes associated with fatty acid synthesis and oxidation [38]. L. plantarum can effectively replace in-feed antibiotic and improve the intestinal health by changing intestinal villus morphology and inhibiting the pathogenic loading [39]. Lactobacillus species effectively absorb and expel heavy metal toxicity from the gastrointestinal tract of broilers [40].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota alteration could influence the intestinal morphology (Louis and Flint, 2009 ; Jahanian et al, 2017 ; Vineetha et al, 2017 ). A negative correlation between the population of caecal B. fragilis and ileal crypt depth was identified by further Pearson correlation analysis.…”
Section: Discussionmentioning
confidence: 99%